A Novel Microbialite-Associated Phototrophic Chloroflexi Lineage Exhibiting a Quasi-Clonal Pattern along Depth. (16th June 2020) - Saghaï, Aurélien; Zivanovic, Yvan; Moreira, David; Tavera, Rosaluz; López-García, Purificación
Abstract: Chloroflexales (Chloroflexi) are typical members of the anoxygenic photosynthesizing component of microbial mats and have mostly been characterized from communities associated to hot springs. Here, we report the assembly of five metagenome-assembled genomes (MAGs) of a novel lineage of Chloroflexales found in mesophilic lithifying microbial mats (microbialites) in Lake Alchichica (Mexico). Genomic and phylogenetic analyses revealed that the bins shared 92% of their genes, and these genes were nearly identical despite being assembled from samples collected along a depth gradient (1–15 m depth). We tentatively name this lineage Candidatus Lithoflexus mexicanus . Metabolic predictions based on the MAGs suggest that these chlorosome-lacking mixotrophs share features in central carbon metabolism, electron transport, and adaptations to life under oxic and anoxic conditions, with members of two related lineages, Chloroflexineae and Roseiflexineae. Contrasting with the other diverse microbialite community members, which display much lower genomic conservation along the depth gradient, Ca. L. mexicanus MAGs exhibit remarkable similarity. This might reflect a particular flexibility to acclimate to varying light conditions with depth or the capacity to occupy a very specific spatial ecological niche in microbialites from different depths. Alternatively, Ca. L. mexicanus may also have the ability to modulate its gene expression as a function of the local environmental conditions during diel cycles in microbialites along the depth gradient.